2006
DOI: 10.1210/jc.2006-1079
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of the Serum Gonadotropin Surge, Inhibins, and Anti-Müllerian Hormone in Normal Newborn Males during the First Month of Life

Abstract: Sertoli cell markers AMH and inhibin B are the earliest useful markers indicating the existence of normal testicular tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
164
2
14

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(184 citation statements)
references
References 47 publications
4
164
2
14
Order By: Relevance
“…This could be due to differences in hormone levels according to different assay platforms (23). Nevertheless, the reported levels of T in the control infants in the two KS studies were much higher (4-20 nmol/l (5th-95th percentiles); (14, 15)) than reported by any other study (2,3,5,(24)(25)(26)(27)(28), including this study.…”
Section: Discussioncontrasting
confidence: 69%
“…This could be due to differences in hormone levels according to different assay platforms (23). Nevertheless, the reported levels of T in the control infants in the two KS studies were much higher (4-20 nmol/l (5th-95th percentiles); (14, 15)) than reported by any other study (2,3,5,(24)(25)(26)(27)(28), including this study.…”
Section: Discussioncontrasting
confidence: 69%
“…These cases can be confirmed by hormonal investigations if done before the age of 6 months -the only period of childhood during which testosterone and gonadotropin deficiencies can be documented (20)(21)(22)(23). Indeed, given the 'physiological' gonadotropin deficiency characteristic of childhood after the sixth month of life, the diagnosis can only be suspected on the basis of cryptorchidism and/or micropenis, sometimes associated with signs pointing to a particular cause.…”
Section: Clinical Presentationmentioning
confidence: 97%
“…22,23 Usually, LH-induced serum testosterone concentrations surge during the fi rst few months of life-a so-called mini-puberty. 24,25 This profi le, however, cannot be used to diagnose complete androgen insensitivity syndrome in many infants, although serum testosterone concentrations do increase appropriately after stimulation with human chorionic gonadotropin. 22 Infants with partial androgen insensitivity syndrome have a more responsive pattern of LH and testosterone, both basally and after stimulation with human chorionic gonadotropin.…”
Section: Endocrine Featuresmentioning
confidence: 99%
“…Serum antimüllerian hormone concentrations also rise in the neonatal period and are sexually dimorphic. 24,26,27 Serum antimüllerian hormone measurement not only suggests the presence of testes in complete androgen insensitivity syndrome, but also that concentrations are higher in infants with the syndrome than in male infants. 28 during the fetal and neonatal stages of testis development.…”
Section: Endocrine Featuresmentioning
confidence: 99%